Qlik Sense : Advanced Data Visualization for Your Organization : Create smart data visualizations and predictive analytics solutions /: Advanced Data Visualization for Your Organization : Create smart data visualizations and predictive analytics solutions. (2017) - Pagans, Ferran Garcia; Kharpate, Neeraj; Cronström, Henric; Richardson, James; Hand, Philip
No abstract available